What is the solution to this system of equations?
x + y – 2z = 2
3x + 3y – 6z = 6
-2x – 2y + 4z = -4

Answer: infinitely many solutions

Step-by-step explanation:

Let’s see what we have here. We have:

x + y – 2z = 2

3x + 3y – 6z = 6

-2x -2y + 4z = -4

Upon looking further we can see that all the equations are the same. When we multiply the first one by 3 we get the second equation. And when we multiply the first one by -2 we get the third equation. Therefore there are infinitely many solutions.

(Make sure to check this because I am still a beginner)

Answer: infinitely many solutionsStep-by-step explanation:infinitely many solutions.